The Development of Science Domain Based Learning Media Tool Which is Integrated with Local Wisdom to Improve Science Process Skill and Scientific Attitude - Dwianto, A.; Wilujeng, I.; Prasetyo, Z. K.; Suryadarma, I G. P. (Jurnal Pendidikan IPA Indonesia, 2017)
This research was conducted to : (1) improve the science domain based learning media which is integrated with appropriate local potention for Science learning material âObject Change Around Usâ for students grade VII of Junior High School, (2) know the effectiveness of science based learning media which is integrated with developed local potention to improve science process skill and scientific attitude of students grade VII of Junior High School. This research was a research and development which adapt 4D Thiagarajan model which include four steps, they were: (1) define, (2) design, (3) develop, and (4) disseminate and Borg & Gall development model which was done into 7 steps, they were: (1) research and information collecting, (2) planning, (3) developing preliminarry form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing, and (7) operational product revision. The research result showed thet the science domain based learning media which was integrated with developed local potention were: (1) appropriate to be used for science learning material âObject Change around usâ for students grade VII of JHS, (2) effective to improve science process skill and scientific attitude of students grade VII of JHS.